Aplikasi Pupuk Kascing dan Bio Urine Sapi terhadap Pertumbuhan dan Hasil Kailan (Brassica oleraceae var.Achepala) - Utami, Sri; Barus, Wan Arfiani; Amalia, Dinda (JURNAL AGROPLASMA, 2024)
Kailan is a vegetable crop that has a high selling value. Efforts to improve the quality of crop yields can be made by applying organic fertilizers to meet plant nutrients and improve soil fertility. This study aims to determine the effect of vermicompost fertilizer and cow bio urine on the growth and yield of kailan plants. The research was conducted the farmland of Lubuk Pakam Batang Kuis road, Deli Serdang Regency with an altitude of ± 27 meters above sea level. The research method used is Factorial Randomized Group Design (RAK) consisting of 2 factors, namely fertilizer kascing (P) with 4 levels, namely: P0 = Control, P1 = 150 g / polybag, P2 = 300 g / polybag, P3 = 450 g / polybag and cow bio urine (B) with 3 levels namely: B1 = 200 ml/liter of water, B2 = 400 ml/liter of water, B3 = 600 ml/liter of water. Parameters measured were number of leaves, leaf area, leaf chlorophyll, plant wet weight, and harvest index. The results showed that the application of 300 g/polybag of vermicompost fertilizer significantly increased leaf area and plant wet weight, the application of 600 ml/liter of cow urine significantly increased total leaf chlorophyll. There was no interaction of the combination of the two treatments on the growth and yield of kailan. Keywords: vegetable crop, baby kailan, fertilizer kascing, cow bio urine, crop yield